2014
DOI: 10.1016/j.bbamem.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Human heat shock protein 70 (Hsp70) as a peripheral membrane protein

Abstract: While a significant fraction of heat shock protein 70 (Hsp70) is membrane associated in lysosomes, mitochondria, and the outer surface of cancer cells, the mechanisms of interaction have remained elusive, with no conclusive demonstration of a protein receptor. Hsp70 contains two Trps, W90 and W580, in its N-terminal nucleotide binding domain (NBD), and the C-terminal substrate binding domain (SBD), respectively. Our fluorescence spectroscopy study using Hsp70 and its W90F and W580F mutants, and Hsp70-∆SBD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 96 publications
9
56
2
Order By: Relevance
“…Although these results are congruent with previous reports on different Hsp70s showing that both protein domains are important for the association of the chaperone with lipids and this association is lipid-specific (Mamelak and Lingwood 2001;) Mamelak and Lingwood 2001;Sahu et al 2011) (Armijo et al 2014;Harada et al 2007Harada et al , 2014Harada et al , 2015Mahalka et al 2014), they do not directly show which part of the protein embeds in the lipid bilayer. However, Armijo et al (2014) showed that in the case of PS, the SBD region of HspA1A embeds within the lipid bilayer.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Although these results are congruent with previous reports on different Hsp70s showing that both protein domains are important for the association of the chaperone with lipids and this association is lipid-specific (Mamelak and Lingwood 2001;) Mamelak and Lingwood 2001;Sahu et al 2011) (Armijo et al 2014;Harada et al 2007Harada et al , 2014Harada et al , 2015Mahalka et al 2014), they do not directly show which part of the protein embeds in the lipid bilayer. However, Armijo et al (2014) showed that in the case of PS, the SBD region of HspA1A embeds within the lipid bilayer.…”
Section: Discussionsupporting
confidence: 77%
“…This initial report was followed by many investigators showing that several members of the Hsp70 protein family, including HspA1A, as well as several bacterial Hsp70 (DnaK) proteins interact specifically with multiple glycolipids and phospholipids. These include phosphatidylserine (PS), bis-(monoacylglycero)-phosphate (BMP), globoyltriaosyl-ceramide (Gb3), sulfo-glycolipids, and anandamide (Arispe and De Maio 2000;Arispe et al 2002Arispe et al , 2004Armijo et al 2014;Broquet et al 2003;Browne et al 2007;Chen et al 2005;Gehrmann et al 2008;Harada et al 2007Harada et al , 2014Harada et al , 2015Kirkegaard et al 2010;Mahalka et al 2014;McCallister et al 2015;Oddi et al 2009;Petersen et al 2010;Whetstone and Lingwood 2003). These reports demonstrate that, although Hsp70s do not contain known lipid-binding domains, they interact with specific lipids and this interaction is evolutionarily conserved.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations